PERTIMBANGAN ETIKA DALAM DISTRIBUSI ORGAN TRANSPLANTASI: TINJAUAN LITERATUR TERHADAP PRINSIP KEADILAN DAN PRIORITAS MEDIS - Alya Syab Baiturrahmi; Mutiara Anissa; Dessy Abdullah; Anita Darmayanti (Nusantara Hasana Journal, 2025)
Organ transplantation is a vital medical solution that faces complex ethical dilemmas in the distribution of limited organs. This study aims to explore and analyze ethical considerations in the distribution of transplanted organs, focusing on the principles of justice and medical priority through a systematic literature review. The search methodology was conducted in the PubMed, ScienceDirect, and Google Scholar databases using the keywords "ethical considerations," "organ transplantation," "justice principles," and "medical priority" for articles published between 2015 and 2025. The principle of distributive justice in organ transplantation integrates multiple criteria that include medical urgency, likelihood of success, age, and healthy lifestyle, while rejecting discriminatory criteria such as economic status or gender. Medical priority influences transplant decisions through systems such as MELD, which emphasize medical urgency but create a dilemma between saving the most critical patients versus optimizing long-term success. Consensus across perspectives indicates that organ transplantation is ethically and religiously acceptable under certain conditions by fulfilling the principles of autonomy, beneficence, non-maleficence, and justice. The findings indicate the need for a framework that harmonizes principles of distributive justice with medical priorities within the context of local cultural and religious values. Practical implications include developing more comprehensive organ distribution guidelines, enhancing the capacity of healthcare professionals in ethical decision-making, and strengthening regulatory systems that accommodate multi-criteria complexity without compromising the principle of justice.